On an initial-boundary value problem for the nonlinear Schrödinger equation - Herbert Gajewski (International Journal of Mathematics and Mathematical Sciences)
We study an initial-boundary value problem for the nonlinear Schrödinger equation, a simple mathematical model for the interaction between electromagnetic waves and a plasma layer. We prove a global existence and uniqueness theorem and establish a Galerkin method for solving numerically the problem.